Investing in the Future: Clean Energy, Technological Advancement, and Environmental Quality as Catalysts for Foreign Direct Investment: Evidence from SSA - Qamruzzaman, Md; Monika, Monika; Avantika, Ramisa Rutbata Hossain; Gupta, Ashish; Kler, Rajnish; Bhuiyan, Rajin Al-Tanjim (International Journal of Energy Economics and Policy, 2025)
This study investigates the influence of clean energy, technological innovation, and environmental quality on foreign direct investment (FDI) inflows in sub-Saharan Africa (SSA). Employing panel data from 2004 to 2022 across SSA countries, the study applies advanced econometric models, including CS-ARDL, DOLS, panel cointegration, and Dumitrescu-Hurlin causality tests to assess long- and short-term dynamics. The results reveal a strong long-run cointegration between FDI and clean energy, technology, and environmental quality. Clean energy infrastructure and technological advancements are positively associated with FDI inflows in the short and long terms. Environmental quality, proxied by CO2 emissions and institutional strength, exhibits bidirectional causality with FDI, indicating a mutual reinforcement. Education and institutional quality exert unidirectional impacts on FDI, suggesting their foundational roles in fostering investment readiness. These relationships underscore the importance of aligning national strategies with sustainable development goals to attract ESG-conscious investors, particularly in contexts with improved environmental governance and innovation ecosystems. Unlike prior research focusing on isolated determinants, this study triangulates clean energy, technology, and environmental governance within a unified framework to address their interactive effects on FDI. It introduces a sustainability-driven model tailored to SSA, offering an empirical foundation for evaluating long-run equilibrium and causality among ESG-relevant variables in developing regions. SSA governments should incentivize clean energy, fortify environmental regulations, and invest in digital infrastructure and education to enhance investor confidence and ensure that FDI aligns with inclusive and sustainable growth trajectories.